2011
DOI: 10.1590/s1516-35982011000400013
|View full text |Cite
|
Sign up to set email alerts
|

Requirements of digestible methionine + cystine for broiler chickens at 1 to 42 days of age

Abstract: -The objective of this work was to estimate requirements of digestible methionine + cystine for broiler chickens from 1 to 42 days of age. It was carried out four experiments for each one of the following phases: pre-initial, initial, growing and final. The birds were distributed in a completely randomized experimental design, with six treatments and six replicates. Treatments consisted of a basal feed for each phase, deficient in digestible methionine + cystine and supplemented with DL-methionine to supply si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 13 publications
6
18
1
1
Order By: Relevance
“…Contrary to the observations of the present study, Ghazanfari et al (2010) observed that in broilers that incremental changes in dietary protein levels did increase feed intake and improved weight gain and feed conversion, compared with a low level of protein in the diet. Jafarnejad et al Improved productive performance of broiler chickens has been observed when increased over NRC recommendation the levels of lysine (Oliveira et al, 2013;Bernal et al, 2014;Quadros et al, 2019;Zarghi et al, 2020) and methionine plus cystine (Goulart et al, 2011). In the current study, the increase in crude protein increased the lysine concentration in the diets over the NRC recommendations; however, the crude protein increase in diets did not have evident increase on the levels methionine plus cystine in the used diets over the NRC recommendations.…”
Section: Growth Performancecontrasting
confidence: 47%
“…Contrary to the observations of the present study, Ghazanfari et al (2010) observed that in broilers that incremental changes in dietary protein levels did increase feed intake and improved weight gain and feed conversion, compared with a low level of protein in the diet. Jafarnejad et al Improved productive performance of broiler chickens has been observed when increased over NRC recommendation the levels of lysine (Oliveira et al, 2013;Bernal et al, 2014;Quadros et al, 2019;Zarghi et al, 2020) and methionine plus cystine (Goulart et al, 2011). In the current study, the increase in crude protein increased the lysine concentration in the diets over the NRC recommendations; however, the crude protein increase in diets did not have evident increase on the levels methionine plus cystine in the used diets over the NRC recommendations.…”
Section: Growth Performancecontrasting
confidence: 47%
“…However, this fact occurs if the relationship between the lysine and other amino acids is respected, especially the sulfur-containing, as also the nitrogen balance of diets on this stage (Trindade Neto et al, 2009;Goulart et al, 2011). The mentioned balance between lysine and other amino acids was not applied in the present research.…”
Section: Resultsmentioning
confidence: 80%
“…The feed intake was calculated by the difference between feed supplied and refusal at each period. The feed conversion ratio (FCR) was calculated by dividing feed intake by weight gain [16].…”
Section: Growth Performancementioning
confidence: 99%